Extensive paralogism in the environmental pangenome: a key factor in the ecological success of natural SAR11 populations - Carmen Molina-Pardines; Jose M. Haro-Moreno; Francisco Rodriguez-Valera; Mario López-Pérez (Microbiome)
Abstract Background The oceanic microbiome is dominated by members of the SAR11 clade. Despite their abundance, challenges in recovering the full genetic diversity of natural populations have hindered our understanding of the eco-evolutionary mechanisms driving intra-species variation. In this study, we employed a combination of single-amplified genomes and long-read metagenomics to recover the genomic diversity of natural populations within the SAR11 genomospecies Ia.3/VII, the dominant group in the Mediterranean Sea. Results The reconstruction of the first complete genome within this genomospecies revealed that the core genome represents a significant proportion of the genome (~ 81%), with highly divergent areas that allow for greater strain-dependent metabolic flexibility. The flexible genome was concentrated in small regions, typically containing a single gene, and was located in equivalent regions within the genomospecies. Each variable region was associated with a specific set of genes that, despite exhibiting some divergence, maintained equivalent biological functionality within the population. The environmental pangenome is large and enriched in genes involved in nutrient transport, as well as cell wall synthesis and modification, showing an extremely high degree of functional redundancy in the flexible genome (i.e. paralogisms). Conclusions This genomic architecture promotes polyclonality, preserving genetic variation within the population. This, in turn, mitigates intraspecific competition and enables the population to thrive under variable environmental conditions and selective pressures. Furthermore, this study demonstrates the power of long-read metagenomics in capturing the full genetic diversity of environmental SAR11 populations, overcoming the limitations of second-generation sequencing technologies in genome assembly. Video Abstract